UJI TOKSISITAS AKUT DARI EKSTRAK ETANOL HERBASEREH (ANDROPOGON CITRATUS D.C ) PADA MENCIT PUTIH SEBAGAI BAHAN PEMBELAJARAN TOKSIKOLOGI - Irawan, Eka Deddy; Ruma K. S., Lusia Oktora; Untari, Sri (Jurnal Pengembangan Pendidikan, 2005)
Sereh Herb have been proven to have effect asanalgetic at mice which have beenÂ induced by acetic acid. In order to develop Sereh herb asÂ  fitofarmaka, it requires acute toxicity testfrom sereh herb to know itâs safety level. Result of this research is expectedto become a studied material of Toxicology. In acute toxicity test of aethanolextract from sereh herb, mice divided into 5 groups which consist of 1 negativecontrol group and 4 dose levels with 2 times interval dose, 200 mg / kg BW, 400mg / kg BW, 800 mg / kg BW, and 1600 mg / kg BW. Up to maximum volume which maybe given to mice, the highest dose given to mice did not caused death,therefore the highest dose expressed as apparent LD50 ( LD0).Thereby, aethanol extract from sereh herb have LD0 value equal to1600 mg / kg BW. If converted to human being with 50 kg BW , LD0aethanol extract from sereh herba become 443,6 g / kg BW. Aethanol extract from sereh herb does not have LD50, this indicate that aethanol extract from sereh herbdoesnt have potention to make toxic effect, this matter is also shown by noany clinical symptom at mice. Thereby acute toxicity potention of Aethanolextract of sereh herb can be classified to relativelynot dangerous (> 15 g / kgBW ). In conclution, safety levelof Aethanol extract from sereh herb relatively safe to be consumed by human being.